Comparative Evaluation of Different Types of Otter Boards in Small Scale Trawling Operations - A.V., Shibu; M., Shahul Hameed (Fishery Technology, 2025)
The cost of construction of different types of otter boards viz., flat rectangular, ’V form and oval slotted otter boards were compared and repair and maintenance charges for each type of otter board during the course of operation were also compared. It was found that, all along the south West Coast, flat rectangular otter boards were preferred by the fishermen. The ’V form otter boards were not popular.